Z-Drugs Prescribing in a Community Mental Health Team Setting in Helensburgh, Scotland: A Cross-Sectional Survey - Felix Kauye; Amanthi Wijesundara; Dalitso Mwandumba (BJPsych Open, 2025)
Aims: Managing insomnia is a common challenge for psychiatrists and their patients. A real-world cohort study on first-line treatment patterns in 265,382 patients with insomnia found that 42.4% of that group were prescribed hypnotic medications. Among those, first prescriptions were most frequently a Z-drug with 35.8% of all patients on these medications. Z-drugs include zolpidem, zopiclone, eszopiclone and zaleplon. We aimed to assess the prevalence and associated factors of Z-drug prescribing in a Community Mental Health Team (CMHT) setting in Helensburgh, Scotland.